2020
DOI: 10.1155/2020/8889055
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Analysis of a Large LNG Tank considering the Effect of Liquid Volume

Abstract: Large Liquefied Natural Gas (LNG) tanks are prone to damage during strong earthquakes, and accurate seismic analysis must be performed during the design phase to prevent secondary disasters. However, the seismic analysis of large LNG tanks is associated with high computational requirements, which cannot be satisfied by the calculation efficiency of traditional analytical techniques such as the Coupled Eulerian–Lagrangian (CEL) method. Thus, this paper aims to employ a less computationally demanding algorithm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Zhao et al They used the Smoothed Particle Hydrodynamics-Finite Element Method (SPH-FEM) algorithm, a less computational algorithm, to simulate liquefied natural gas (LNG) tanks. They stated that the Von Mises tension increased at the bottom of the tank, and that strong earthquakes could seriously compromise the structural integrity of large LNG tanks [22]. In this present study, by observing the sample responses such as acceleration and deformation of the tested models, the results were compared and confirmed with previous studies.…”
Section: Introductionsupporting
confidence: 81%
“…Zhao et al They used the Smoothed Particle Hydrodynamics-Finite Element Method (SPH-FEM) algorithm, a less computational algorithm, to simulate liquefied natural gas (LNG) tanks. They stated that the Von Mises tension increased at the bottom of the tank, and that strong earthquakes could seriously compromise the structural integrity of large LNG tanks [22]. In this present study, by observing the sample responses such as acceleration and deformation of the tested models, the results were compared and confirmed with previous studies.…”
Section: Introductionsupporting
confidence: 81%
“…Therefore, the seismic safety of LNG tanks gains much attention. [1][2][3][4] Ground supported cylindrical tanks are one of commonly used types of tanks, which are without anchorage sometimes in order to realize the economical factor of the structures. When the overturning moment caused by the horizontal earthquake exceeds the restoring moment resulted from self-weight, the tank is lifted from the base.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of impact damage were identified according to dynamic response results such as stress, energy, displacement, and critical impact velocity. Zhang et al [15] investigated the effect of the multi-directional components of ground motion on an unanchored steel storage tank. They concluded that the vertical seismic component produced high compressive axial stress, which caused a significant increase in uplift and sliding at the tank bottom.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the vertical seismic component produced high compressive axial stress, which caused a significant increase in uplift and sliding at the tank bottom. Zhao et al [15] applied an accurate and efficient Smoothed Particle Hydrodynamics-Finite Element Method (SPH-FEM) algorithm to evaluate the seismic response of a 160,000 m 3 LNG prestressed storage tank at different liquid levels. The maximum stress of the inner tank with 100% LNG liquid level exceeded 500 MPa under the selected seismic waves and raised concerns for its structural safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation